2019
DOI: 10.3390/pathogens9010021
|View full text |Cite
|
Sign up to set email alerts
|

Human Microglia Respond to Malaria-Induced Extracellular Vesicles

Abstract: Microglia are the chief immune cells of the brain and have been reported to be activated in severe malaria. Their activation may drive towards neuroinflammation in cerebral malaria. Malaria-infected red blood cell derived-extracellular vesicles (MiREVs) are produced during the blood stage of malaria infection. They mediate intercellular communication and immune regulation, among other functions. During cerebral malaria, the breakdown of the blood–brain barrier can promote the migration of substances such as Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…All symptoms of clinical malaria and in particular its most severe complication, cerebral malaria, are caused by the exponential growth of the parasite during the blood stage, subsequent cytoadherence and sequestration of iRBCs at critical sites in the microvasculature as well as overreactivity of the proinflammatory immune response (51)(52)(53). Therefore, to prevent malaria-associated morbidity and mortality tight control of parasitemia is essential.…”
Section: Discussionmentioning
confidence: 99%
“…All symptoms of clinical malaria and in particular its most severe complication, cerebral malaria, are caused by the exponential growth of the parasite during the blood stage, subsequent cytoadherence and sequestration of iRBCs at critical sites in the microvasculature as well as overreactivity of the proinflammatory immune response (51)(52)(53). Therefore, to prevent malaria-associated morbidity and mortality tight control of parasitemia is essential.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, CD14 + monocytes were identified as the main producers of CXCL-10 when challenged with P. falciparum , but the sub-sets that were involved and the association between CXCL-10 levels and parasite burden in humans remain unknown [ 69 ]. In addition, using an in vitro model of human blood monocyte-derived microglia cells, the uptake of IE-derived extracellular vesicles was shown to cause down-regulation of IL-6 and IL-10 gene expression [ 70 ]. When mouse macrophages were challenged with these vesicles, they produced TNF and up-regulated their CD40 expression [ 71 ].…”
Section: Heterogeneity In Host Phagocyte Subpopulations: Who Is the Big Eater?mentioning
confidence: 99%
“…After the rupture of the BBB, pRBC, EV-pRBC, and molecules such as heme [102] and hemozoin can invade the brain parenchyma and be recognized by microglia [84,103,104]. In ECM, a rapid response of microglial cells occurs with morphological alteration characteristic of microglial activation [90,105,106].…”
Section: Microglial Cellsmentioning
confidence: 99%